Pengaruh Kecerdasan Intelektual, KecerdasanEmosional, Kecerdasan Spiritual, Dan Kecerdasan Sosial Terhadap Pemahaman Akuntansi(Studi Kasus Mahasiswa Program Studi Akuntansi Angkatan Tahun 2011 Di Universitas Sebelas Maret Dan Universitas Muhammadiyah Surakarta) - Asih, Murni; , Dr. Fatchan Achyani, M.Si (2015)
The purpose of this research was to determine the effect of intellectual intelligence, emotional intelligence, spiritual intelligence, and social intelligence to the understanding of accounting. This study uses primary data was by providing the questions in the form of a questionnaire, while secondary data was used to determine the number of students in the class of 2011 Academic. The population in this research were all students who were still active in the Faculty of Economics and Business Department of Accounting University of March (UNS) and Muhammadiyah University of Surakarta (UMS). The number of samples taken in this research were 187 students. Determination of sampling using purposive sampling method. Testing the hypothesis in this study using multiple linear regression method. Simultaneous hypothesis testing results indicate that the variable intellectual, emotional intelligence, spiritual intelligence, and social intelligence have influence together and significantly to the understanding of accounting, visible from Fobs (46.609) was greater than the Ftable (2.421) with significant value 0.000 < α = 0.05. Partial hypothesis testing results indicate that the intellectual intelligence variables affect the understanding of accounting, visible from tobs (2.623) greater than ttable (1.960) with significant value 0.009 <α = 0.05. Emotional intelligence variables affect the understanding of accounting, visible from tobs (4.037) was greater than ttable (1.960) with significant value 0.000 <α = 0.05. Variable spiritual intelligence did not affect the understanding of accounting, looks tobs (0.839) lower than ttable (1,960) with significance 0.403 <α = 0.05. Social intelligence variables affect the understanding of accounting, visible from tobs (6.793) was greater than t table (1.960) with significant value 0.000 <α = 0.05. Coefficient of determination test result obtained for 0,495. Keywords : intellectual intelligence, emotional intelligence, spiritual intelligence, social intelligence, understanding of accounting.